Ethnoecological Perspective on Community Forest Conservation: The Susuk Wangan Ceremony in Setren Village, Wonogiri - Frida Eka Putri; Santhyami Santhyami (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Community-based conservation and traditional ecological knowledge are becoming increasingly vital in biodiversity conservation and sustainability science. Nevertheless, previous ethnoecological research has infrequently incorporated ritual behaviors, ecology elements, and conservation management. This study aimed to analyze the ecological elements and conservation management aspects inherent in the Susuk Wangan tradition in Setren Village, Wonogiri, Indonesia. Methodology: This study utilized a qualitative ethnoecological approach. Data were gathered through observation, documentation, and in-depth interviews with 15 informants selected using purposive sampling. Data were analysed using descriptive analysis techniques, encompassing data condensation, data display, conclusion formulation/verification, and source triangulation. Findings: The findings identified five ecological elements: water source preservation, waterway sanitation, forest vegetation preservation, sustainable forest resource utilization, and wildlife conservation, supported by five conservation management components: local wisdom, customary rules, community participation, institutional regulations, and social-spiritual sanctions. Contribution: This study illustrates that the Susuk Wangan tradition embodies a unified socio-ecological governance framework grounded in traditional knowledge which supports community-based conservation and sustainable forest management in Setren Village, Wonogiri